On creativity - Bohm, David (Routledge classics, 2004)
Creativity is fundamental to human experience. In On Creativity David Bohm, the world-renowned scientist, investigates the phenomenon from all sides: not only the creativity of invention and of imagination but also that of perception and of discovery. This is a remarkable and life-affirming book by one of the most far-sighted thinkers of modern times.